Karakteristik Kimia Fisika Air Dan Tanah Di Hutan Lindung Air Telang Banyuasin Sumatera Selatan - Rangga Rangga; Syaiful Eddy; Andi Arif Setiawan (Environmental Science Journal (esjo) : Jurnal Ilmu Lingkungan, 2026)
Forests are a vital natural resource for human life, nature, and the environment. The Air Telang Protected Forest has unique water and soil characteristics, given that it is a coastal area affected by tidal conditions. The purpose of this study was to analyze the chemical and physical characteristics of water and soil in the Air Telang Protected Forest, Banyuasin, South Sumatra. The parameters used in the water samples were temperature, electrical conductivity (Electrical Conductivity), pH, and salinity. The parameters used in the soil samples were pH, Electrification Capacity (Electrical Conductivity), salinity, and soil water content. The research method used a survey. The results showed that water conditions in the Air Telang Protected Forest varied between stations. The pH tended to be normal, with the highest Electrification Capacity (DHL) at Station 2, and the highest salinity at Station 3. Furthermore, the water temperature gradually increased. The analysis of the chemical and physical parameters of the soil in the Air Telang Protected Forest revealed that Station 2 had the most striking characteristics of the two stations, with low pH, Electrification Capacity (DHL), salinity, and soil water content.